The Effect of Profitability, Company Growth, and Capital Structure on Firm Value (A Case Study of Technology Sector Companies Listed on the Indonesia Stock Exchange for the 2021–2023 Period) - Ni Putu Nina Astadewi; I Gusti Ngurah Agung Suaryana (International Journal of Economics, Management and Accounting, 2025)
Firm value is essential for business sustainability and serves as a key consideration for investors in assessing a company’s prospects. The enhancement of firm value is influenced by various factors observed by both internal and external parties. This study examines the partial effects of profitability, company growth, and capital structure on firm value. The research variables include Return on Assets (ROA) for profitability, Sales Growth for company growth, Debt to Equity Ratio (DER) for capital structure, and Price to Book Value (PBV) for firm value. A quantitative approach was employed using a sample of 25 technology sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period, selected through purposive sampling. Data analysis techniques included descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that profitability and company growth have a negative effect on firm value, while capital structure has a positive effect. These results contradict signaling theory but support the trade-off theory. This research contributes both theoretically and practically to the field of accounting and serves as a reference for management and investors in making strategic decisions related to enhancing firm value.